Liberalisation, discourse and `natural' inequality - DeSouza, Peter Ronald (1996)
Apprehending persistence of power assymetries and corruption under liberalisation discourse, the author examines with egalitarian perspective the concept of equality. Visualising possibility of social inequality getting irreversibly transformed as natural inequality under the impact of market forces, he discusses how it can be resisted through recognition of equality as a protest ideal. - Reproduced
Keywords: Liberalization - India; Economic and social development; Economic liberalization